Improving liming mode for remediation of Cd-contaminated acidic paddy soils: Identifying the optimal soil pH, model and efficacies - Bo Li; Hanhua Zhu; Qihong Zhu; Quan Zhang; Chao Xu; Zebo Fang; Daoyou Huang; Weisheng Xia (Ecotoxicology and Environmental Safety, 2024)
Liming has been widely taken to remediate Cd-contaminated acidic paddy soils, whereas liming mode involving in the relevant optimal soil pH, model and efficacies remain unclear. Both soil and field liming experiments were conducted to improve liming mode for precise remediation of Cd-contaminated acidic paddy soils. Soil batch liming experiments indicated soil DTPA-Cd and CaCl2-Cd were piecewise linearly correlated to soil pH with nodes of 6.8–8.0, and decreased respectively by 15.3%37.7% and 80.7%93.8% (P < 0.05) when soil pH raised over the nodes, indicating an appropriate target soil pH 7.0 for liming. Stepwise linear regression revealed that liming ratio (LR, kg ha−1) could be estimated from soil basal pH (pH0) and the interval to the target soil pH (ΔpH), as [LR=exp(1.10 ×ΔpH+0.61 ×pH0-4.98), R2 = 0.97, n = 42, P < 0.01]. The model exhibited high prediction accuracy (95.2%), low mean estimation error (−0.02) and root mean square error (0.20). Field liming experiment indicated liming to target pH decreased respectively soil CaCl2-Cd by 95.2–98.0% and rice grain Cd by 59.8–80.6% (P < 0.01), whereas uninfluenced rice grain yield. Correlation analysis and structural equation models (SEM) demonstrated that great reduction in Cd phytoavailability was mainly attributed to the transformation of soil water-soluble and exchangeable Cd to carbonate-bound Cd and Fe/Mn oxides-bound Cd and reduced Cd in iron plaque as increasing soil pH. However, rice grain Cd of 50% samples met national food safety standards limit of China (0.2 mg kg−1) due to the high soil Cd level (0.8 mg kg−1). In conclusion, liming to target soil pH 7.0 could be considered as a precise and effective remediation mode for Cd-contaminated acidic paddy soils and complementary practices should be implemented for severe pollution. Our results could provide novel insights on precise liming remediation of Cd-contaminated acidic paddy soils.